Diagnosis of Liquidity in the Indian Infrastructure Industry - A Risk-Return Perspective - Reddy , D Maheswara (Gyan Management Journal, 2014)
Managing liquidity is a matter of management's attitude towards liquidity. Some thought of conservative and other opines aggressive one is fit for all the times. Most of the time failure comes from improper diagnosis of liquidity. The quantum/degree of liquidity is the paramount factor for healthy companies. The degree/magnitude of liquidity means; it is neither high nor low degree of liquidity.Any flaw in this process that will jeopardize the cash flow cycle of the business and it compel the business in liquidity problems. In other words it will affect the name and fame of the organizations, if liquidity turned out into illiquidity. As infrastructure industry is gaining importance in terms of economic and industrial growth, it is high time to assess liquidity management and a trade-off between liquidity, profitability and risk of those prominent companies (i.e high market capitalization) in the infrastructure industry.
Keywords: Current Assets; Current Liabilities; Liquidity; Profitability; Risk